Comparison of KP and BBM-KP Models - Gideon P. Daspan; Michael M. Tom (International Journal of Mathematics and Mathematical Sciences)
It is shown that the solutions of the pure initial-value problem for the KP and regularized KP equations are the same, within the order of accuracy attributable to either, on the time scale 0≤t≤ε−3/2, during which nonlinear and dispersive effects may accumulate to make an order-one relative difference to the wave profiles.